Service learning in preservice teacher education programs - Wise, Sarah Ellen (My University, 2026)
This qualitative case study explored how preservice teachers experience service learning when it is intentionally integrated within a School as Community course. Grounded in experiential learning theory, teacher visioning, and reflective practice, the study followed three participants as they completed the required forty hours of service-learning experiences in their teacher education program. Data were collected from multiple sources guided by the course, including an initial teacher visioning assignment, course goal reflection papers, an end-of-semester field experience reflection paper, and post-semester interviews. Findings revealed that when preservice teachers were enrolled in a course that intentionally incorporated guided reflection assignments, they were better able to connect their lived service-learning experiences with their developing beliefs and understanding about teaching, community, and vocation. Participants described a shift in how they viewed teaching, not simply as a career, but as relational work and a mission-driven profession, with a better understanding of how to connect pedagogy to real life. Engagement in service-learning opportunities, paired with reflective assignments embedded throughout the School as a Community course, deepened participants’ awareness of the school within its community, strengthened their commitment to students, and clarified their motivations for entering the profession. Through reflection, preservice teachers grew in self-awareness, empathy, and alignment between their personal values and their professional development. This study contributes to the literature on service learning in teacher education by highlighting how reflection within a course context increases the meaning and impact of service-learning experiences. The findings suggest that teacher preparation programs should intentionally embed meaningful, guided reflection into service-learning requirements to create purpose-driven, community-oriented educators who see teaching as more than a career.
Keywords: Service learning; Teacher education programs; Teacher education; Preservice teachers; Skills to teacher; Transformational service learning